Illegal - Colfer, Eoin (Sourcebooks Jabberwocky, 2018)
"Ebo is alone. His brother, Kwame, has disappeared, and Ebo knows it can only be to attempt the hazardous journey to Europe, and a better life, the same journey their sister set out on months ago. But Ebo refuses to be left behind in Ghana. Ebo's epic quest takes him across the Sahara Desert to the dangerous streets of Tripoli, and finally out to the merciless sea. But with every step he holds on to his hope for a new life, and a reunion with his family"--Back cover.